Ameliorating the impairment of glucose utilization in a high-fat diet-induced obesity model through the consumption of Tucum do-Cerrado (Bactris Setosa Mart.) - Araújo, Ananda de Mesquita (2024)
Introduction We evaluated the effect of Tucum-do-Cerrado on glucose metabolism homeostasis and its relationship with redox-inflammatory responses in a high-fat (HF) diet-induced obesity model. Results The HF diet increased energy intake, feed efficiency, body weight, muscle and hepatic glycogen, insulin, homeostatic model assessment of insulin resistance (HOMA IR) and beta (β)-cell function, and gut catalase (CAT) activity, and decreased food intake, hepatic glutathione reductase (GR), glutathione peroxidase (GPX), glutathione S-transferase (GST), and superoxide dismutase (SOD) activities, hepatic phosphoenolpyruvate carboxykinase 1 (Pck1), and intestinal solute carrier family 5 member 1 (Slc5a1) mRNA levels compared with the control diet. However, the HF diet with Tucum-do-Cerrado decreased hepatic glycogen, and increased hepatic GR activity, hepatic Slc2a2 mRNA levels and serum Tnfa compared with the HF diet. Tucum-do-Cerrado decreased muscle glycogen, intestinal CAT and GPX activities, muscle PFK-1 and HK activities, and increased hepatic protein (CARB) and intestinal lipid (MDA) oxidation, hepatic GST activity, serum antioxidant potential, hepatic phosphofructokinase-1 (PFK-1) activity, intestinal solute carrier family 2 member 2 (Slc2a2), tumor necrosis factor (Tnf), interleukin-1 beta (Il1b), muscle protein kinase AMP-activated alpha 1 (Prkaa1), solute carrier family 2 member 2 (Slc2a2) mRNA levels, and serum interleukin-6 (IL-6) levels, regardless of diet type. Conclusion Tucum-do-Cerrado consumption may ameliorate impaired glucose utilization in a HF diet-induced obesity model by increasing liver and muscle glucose uptake and oxidation. These data suggest that Tucum-do-Cerrado consumption improves muscle glucose oxidation in non-obese and obese rats. This response may be related to the improvement in the total antioxidant capacity of rats.